2009
DOI: 10.3797/scipharm.0806-08
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and In Vitro Evaluation of A Pegylated Nano-Liposomal Formulation Containing Docetaxel

Abstract: An improved pegylated liposomal formulation of docetaxel has been developed with the purpose of improving the docetaxel solubility without any need to use tween80 that is responsible for hypersensitivities following administration. Liposomes all had spherical shape with size of 130-160 nm. The most important finding of this study is that pegylated liposomes were prepared with significant increase in docetaxel encapsulation efficiency and stability of the formulation in comparison with last reports on docetaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 24 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…This SEM morphology was similar to that reported in the literature on LS comprising phospholipids and cholesterol. 26 In this study, the encapsulation efficiency of QU in QU-LS was 52.61%±3.27% at r SA =5% (n=3). QU in methanol was added to and incorporated in a lipid thin film via hydrophobic affinity.…”
Section: Statisticsmentioning
confidence: 49%
“…This SEM morphology was similar to that reported in the literature on LS comprising phospholipids and cholesterol. 26 In this study, the encapsulation efficiency of QU in QU-LS was 52.61%±3.27% at r SA =5% (n=3). QU in methanol was added to and incorporated in a lipid thin film via hydrophobic affinity.…”
Section: Statisticsmentioning
confidence: 49%
“…Hence, it has been considered for further physicochemical characterization and different in vitro and in vivo pharmacokinetic studies. DTX is an approved drug to tumor of brain in combination therapy, but its entry to the brain is prevented by BBB due to its different physiochemical and pharmacological factors (Chen et al, 2004;van Rooy et al, 2011).We have tried to deliver DTX by incorporating it into the liposomes, based on the hypothesis that the nanosize of the vesicle may help to deliver DTX and the use of nanoliposomes may overcome the solubility problem of DTX and reported toxicity of Taxotere Õ , the marketed formulation (Yang et al, 2007;Yousefi et al, 2009;Costantino & Boraschi, 2012). In this work we have formulated nanoliposomes of DTX using SPC as lipid component, and CHL as a stabilizer of lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Several stability and drug payload studies on the NP formulations have shown that they are highly stable with high carrier capacity, are feasible for incorporation of both hydrophilic and hydrophobic substances, and can be administered by various routes, including oral application and inhalation. 35,36 NPs have been designed for optimal size and surface characteristics to increase their circulation time in the bloodstream and their biodistribution. They are also able to carry their loaded active drugs to cancer cells by selectively using the unique pathophysiology of tumors, such as their enhanced permeability and retention effect and the tumor microenvironment.…”
Section: Current Status Of Nanomaterial-based Drug-delivery Systemsmentioning
confidence: 99%